Tanzania : Can Local Communities Successfully Run Cash Transfer Programs? - World Bank (Washington, DC, 2015)
In Tanzania, an innovative conditional cash transfer program that relies on local communities to administer the payments has succeeded in helping the countrys poorest citizens. But these programs generally require strong central government bureaucracies to administer the program and transfer the payments, potentially limiting the use of these programs where governments are less experienced or stable. Development experts are interested in new models for delivering cash transfers in countries with weak or inexperienced central governments. One possibility is to rely on communities themselves, rather than a central bureaucracy, to administer the cash transfers. But can communities run the programs as efficiently and ensure that benefits are equally and regularly distributed? Community-based conditional cash transfers have proven to be an effective tool for alleviating poverty and improving health and education outcomes for the poor. These are important lessons for development experts and should provide much-needed evidence for policy makers looking to expand social safety net programs in low income countries. As the results of a recent impact evaluation indicate, cash transfer systems can be adapted to work well in low-income countries that do not have a strong central government to administer them. Community groups, provided they are given proper training and adequate support, can handle the logistics of the cash transfers, and in doing so, help improve the lives of their poorest neighbors. This Evidence to Policy note was jointly produced by the World Bank Group, the Strategic Impact Evaluation Fund (SIEF), and the British governments Department for International Development.